"The world is so white": improving cultural safety in healthcare systems for Australian Indigenous people with rheumatic heart disease. (19th July 2022) - Mitchell, Alice; Wade, Vicki; Haynes, Emma; Katzenellenbogen, Judith; Bessarab, Dawn
Abstract: Objective : To examine the views of senior health system knowledge holders, including Aboriginal experts, regarding the spaces where elimination strategies for rheumatic heart disease take place: Aboriginal and Torres Strait Islander ways of knowing, being and doing; and biomedical healthcare models. We aimed to support the implementation of the RHD Endgame Strategy by providing some of the 'how'. Methods : In‐depth interviews were undertaken with 23 participants. The design of the interview questions and analysis of the data used strengths‐based approaches as directed by Aboriginal researchers. Results : Given the dominance of the biomedical worldview, and the complex trajectory of RHD, there is significant tension in the intersection of worldviews. Tensions that limit productive dialogue are juxtaposed with suggestions on how to reduce tension through reflexivity, power shifting and endorsing Aboriginal leadership and governance. Evidence supported cultural safety for RHD care, prevention and elimination as the key action. Conclusions : Recommendations include addressing power imbalances between dominant and minority populations throughout the health system; reform that both supports and is supported by Non‐Indigenous and Aboriginal and Torres Strait Islander leadership. Implications for public health : Increased understanding of and support for Indigenous leadership and cultural safety will enable implementation of the new RHD strategy.